IMPORTANCE OF CYBERSECURITY IN DIGITAL BANKING ERA (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
This article emphasizes the significance of cybersecurity in the context of digital banking. It highlights the potential consequences of security breaches, such as financial loss, identity theft, and reputational damage for both banks and their customers. The article may discuss the evolving nature of cyber threats, including phishing, malware, ransomware, and social engineering techniques, and how they specifically target the banking sector. Furthermore, the article may delve into the various cybersecurity measures and best practices that banks should adopt to mitigate risks. This could include implementing robust encryption protocols, multi-factor authentication, regular security audits, employee training programs, and establishing incident response plans. The importance of collaboration between banks, regulatory bodies, and cybersecurity experts may also be emphasized in the article. It may highlight the need for continuous monitoring, threat intelligence sharing, and staying updated with the latest security technologies and trends.